Integrating Action Theory and Human Agency in Career Development - Chen, Charles P. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article proposes the integration of action theory and the notion of human agency in life and career. A review of the theoretical and research background of the two perspectives forms a conceptual basis for discussion and analysis. The article then compares some aspects of the two perspectives, recognizing variation while focusing more on the common conceptual ground they share. Career counselling implications are provided with the goal of enhancing persons' action orientation and agentic functioning in their life career development.